Descriptive Study Of Internet Based Learning And Diabetic Care Management Among Patients At Putrajaya Hospital - Mohammed, Azman (2007)
The objective of this study is to examine the association, occupation and household income have significant association between internet internet access and diabetic care management. This study was conducted in Putrajaya Hospital with 100 respondents (N=100) with Diabetes Type 2 from 3rd May to 28 June 2007. Self administered questionnaire was used as study instrument.